Are there specific factors that increase the possibility of success for university spin-off companies? A longitudinal study of 50 companies over nineteen years. (1st September 2018) - Jonsson, Lars; Santurio, Mateo; Micucci, Patrick
By a longitudinal analysis of all university spin-offs (USOs) created through the Holding Company of Uppsala University, Sweden, during the nineteen-year period between 1998 and 2016, we compare existing literature to our empirical data to identify factors that increase the probability for success. During the period studied, 82 companies were formed, of which 55 were defined as USOs and 50 were mature enough to be analysed. The overall survival rate was 78 per cent and fifteen USOs fulfilled the defined criteria as being successful while fourteen were considered failures. Using descriptive statistics, we concluded that the successful USOs had a surrogate entrepreneur almost six times more often and had been incubated 3.4 times more often than the failing ones. The two major barriers to overcome for a USO during its development seem to be to have a clear entrepreneurial commitment in the founding team of researchers and to overcome the so-called 'threshold of credibility'. The latter corresponds to the challenge for a new venture to be accepted and embedded in the existing business network, which is crucial to be able to reach sustainable returns.